Sistem Hukum Nasional Indonesia Ditinjau Dari Pancasila Dan UUD 1945 - Anna Maudina Manurung; Della Puspita; Della Septi Sari; Mutiara Azzahra Lubis; Nur Wida Yani; Tri Mei Rosalya Purba (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The National Legal System currently being built is the Pancasila Legal System, namely a legal system based on the 1945 Constitution of the Unitary State of the Republic of Indonesia with the spirit of Pancasila. The aim of this research is to clarify the national legal system from the perspective of Pancasila and the 1945 Constitution. The methodology of this library reseach will explain Pancasila values from the national legal system and in statutory regulations which can be reviewed comprehensively in this paper. The results of this research will explain the need for the development of a sustainable national legal system with the character of the Indonesian nation based on legislation and Pancasila. To understand the national legal system well, you must first be equipped with the basics. This is important as a first step in studying the national legal system in more depth.